Point of Care Ultrasound Diagnosis of a Massive Thoracoabdominal Aortic Aneurysm - Yee, Allison M (Cureus, 2017)
This report highlights an atypical presentation of extensive thoracoabdominal aortic aneurysm with intramural hematoma and transient paralysis of the lower extremities. Clinical suspicion for aortic pathology prompted a point of care ultrasound of the heart and aorta, which demonstrated a thoracic and abdominal aortic aneurysm with intraluminal pathology. Consultation and transfer to a tertiary care facility was based solely on the emergency physician’s ultrasound. Subsequent computed tomography (CT) imaging confirmed the ultrasound findings and discovered a left common iliac artery thrombosis consistent with the patient’s presentation. Point of care ultrasound can help clinicians diagnose aortic pathology and direct patient care efficiently and effectively.